Counting and Size Classification of Active Soil Bacteria by Fluorescence In Situ Hybridization with an rRNA Oligonucleotide Probe - Christensen, Henrik (American Society for Microbiology, 1999)
A fluorescence in situ hybridization (FISH) technique based on binding of a rhodamine-labelled oligonucleotide probe to 16S rRNA was used to estimate the numbers of ribosome-rich bacteria in soil samples. Such bacteria, which have high cellular rRNA contents, were assumed to be active (and growing) in the soil. Hybridization to an rRNA probe, EUB338, for the domain Bacteria was performed with a soil slurry, and this was followed by collection of the bacteria by membrane filtration (pore size, 0.2 μm). A nonsense probe, NONEUB338 (which has a nucleotide sequence complementary to the nucleotide sequence of probe EUB338), was used as a control for nonspecific staining. Counting and size classification into groups of small, medium, and large bacteria were performed by fluorescence microscopy. To compensate for a difference in the relative staining intensities of the probes and for binding by the rhodamine part of the probe, control experiments in which excess unlabelled probe was added were performed. This resulted in lower counts with EUB338 but not with NONEUB338, indicating that nonspecific staining was due to binding of rhodamine to the bacteria. A value of 4.8 × 10(8) active bacteria per g of dry soil was obtained for bulk soil incubated for 2 days with 0.3% glucose. In comparison, a value of 3.8 × 10(8) active bacteria per g of dry soil was obtained for soil which had been air dried and subsequently rewetted. In both soils, the majority (68 to 77%) of actively growing bacteria were members of the smallest size class (cell width, 0.25 to 0.5 μm), but the active (and growing) bacteria still represented only approximately 5% of the total bacterial population determined by DAPI (4′,6-diamidino-2-phenylindole) staining. The FISH technique in which slurry hybridization is used holds great promise for use with phylogenetic probes and for automatic counting of soil bacteria.